Targeting Thyroid Hormone/Thyroid Hormone Receptor Axis: An Attractive Therapy Strategy in Liver Diseases - Tang, Qianyu; Zeng, Min; Chen, Linxi; Fu, Nian (Frontiers in Pharmacology, 2022)
Thyroid hormone/Thyroid hormone receptor (TH/TR) axis is characterized by TH with the assistance of plasma membrane transporters to combine with TR and mediate biological activities. Growing evidence suggests that TH/TR participates in plenty of hepatic metabolism. Thus, this review focuses on the role of TH/TR axis in the liver diseases. To be specific, the TH/TR axis improves metabolic-associated fatty liver disease, hepatocellular carcinoma, hepatitis, liver fibrosis and liver injury while exacerbates the progression of acute liver failure. Also, TH/TR axis has paradoxical roles in alcoholic liver disease. TH/TR axis may be a prospecting target to cure hepatic diseases.